Development of roselle (Hibiscus sabdariffa) wine. - Lagtapon, Jyll Flores
Roselle (Hibiscus sabdariffa) is underutilized but is promising due to its antioxidative properties. The study focused on the development of roselle wine to add and increase the value and quality of the product. Effect of different sugar concentrations and ratio of roselle extract to water was analyzed through physical and chemical analysis such as total soluble solids pH, titrable acidity and alcohol content. It was found next that total soluble solids for the 20 g/ 100 ml substrate for 30:70, 50:50 and 60:40 ratio were 11.23°B, 12.37°B and 12.87°B, respectively. Total soluble solids for 25 g/ 100 ml substrate for 30:70, 50:50 and 60:40 ratio were 14.13°B, 15.43°B and 16.8°B, respectively. The pH for the 20g/100 ml formulation for the 30:70, 50;50 and 60:40 ratio were 3.13, 3.03 and 2.99 respectively while the mean pH values for the 25g/100 ml formulation were 3.08, 3.02 and 2.95 respectively. The mean titrable acidity values for the 20g/100ml formulation for 30:70, 50;50 and 60:40 were 0.37%, 0.46% and 0.51%, respectively and 0.40%, 0.48% and 0.54% respectively for the 25g/100ml formulation. Mean alcohol content values, expressed is % ABW for the 20g/100 ml formulation for 30:70, 50:50, and 60:40 ratio were 3.87, 3.18 and 3.23 respectively while mean values for the 25g/100 ml formulation were 3.77, 4.25 and 4.75 respectively. Sensorial property was also assessed using rank test for preference to determine the most preferred wine (MPW) from the two different sugar concentrations. Paired preference for comparison test was used to determine which of the two MPWs from different sugar concentrations was most preferred. Results showed that formulation R2C2 was most preferred. Results of the sensory evaluation showed that the most preferred wine wasthe 50:50 roselle extract to water ratio formulation with 25 grams sugar per 100 ml concentration. The MPW was liked moderately. Sensory properties of MPW were determined with hedonic scale and line scale interval. The sensory attributes of the MPW was perceived by the twenty panelists to be dark red, with a perceptible tart aroma and a blend of slightly sweet and sour and slightly astringent taste. Clarity of the MPW was also evaluated and was judged to be very clear. Generally, roselle wine can be produced with formulation of 50:50 roselle extract to water ratio and 20 g/ 100 ml sugar concentration. This study also showed that roselle wine has a potential market value.